An analysis and evaluation of two English textbooks for second graders of junior high school - Anita Nur Masyi'ah; Dyah Setyowati Ciptaningrum (LingTera, 2018)
This study aimed at: (1) discovering the textbooks quality based on the criteria from some ELT experts and Pusat Perbukuan, and (2) identifying the strengths and weaknesses of students’ textbooks entitled When English Rings a Bell and Bright for Grade VIII. The data were collected using checklists which were distributed to two English teachers and the researcher. The scores then were accumulated to find the average and after that the final score was rated using the category from Pusat Perbukuan and ELT experts. The results showed that When English Rings a Bell has fulfilled the criteria of a fair textbook (78.6%). The book has some strengths and weaknesses, such as providing materials covering the local culture, lacking some retention, and the like. Meanwhile, Bright has fulfilled the criteria of a good textbook (87.2%) with some strengths and weaknesses, such as providing materials containing target culture, lacking materials containing local culture.